Histological changes in female mice kidneys as a result of Valproic acid drug treatment - Elturshani, Omelaz A. M.; Al-Sarraj, Khalida R.; Guseibat, Tarek A.; El-nagaz, El-nagi O. M.; El-Tarhouni, Amal (Journal of Pure & Applied Sciences, 2021)
Valproic acid is a broad  spectrum anti- convulsant drug,  established as a long – term treatment for epilepsy and has toxic effect on kidney tissues. This study aimed to investigate the histological changes that may occur in the kidney in association with prolonged administration and overdose treatment of valproic acid. 35 albino mice were used, they were divided into four groups, group(I) included 5 animals and served as control group, group(II) included 10 animals and given progressive doses of valproic acid for ten weeks, starting with (15mg/kg/day) as minimum recommended dose and ending with (60mg/kg/day) as maximum recommended dose, group(III) included 10 animals and received an overdose (120mg/kg/day) for one week, group(IV) included 10 animals and treated exactly as group(II) then the animals were left for recovery for three weeks. The animals were sacrificed at the end of each period and the kidney tissue was excised. The drug induced many histological changes in kidney tissues, including inflammatory cellular infiltration, cell necrosis, cloudy swelling, hydropic degeneration, hemorrhage areas, oedema, and collagen deposition. The study concluded that valproic acid has multiple toxic effects on kidney tissues as far as the histological studies concerned and the effects were dependent on the dose and on the duration of treatment. Incomplete recovery was recorded after discontinuation of the drug.